First-In-Human, First-In-Class, Phase I Trial of the Fucosylation Inhibitor SGN-2FF in Patients with Advanced Solid Tumors. (22nd September 2021) - Do, Khanh T.; Chow, Laura Quan Man; Reckamp, Karen; Sanborn, Rachel E.; Burris, Howard; Robert, Francisco; Camidge, D. Ross; Steuer, Conor E.; Strickler, John H.; Weise, Amy; Specht, Jennifer M.; Gutierrez, Martin; et al.
Abstract : Lessons Learned: Inhibition of glycoprotein fucosylation, as monotherapy and in combination with immune checkpoint blockade, is a promising therapeutic strategy for treating a broad range of cancers. In this first-in-human, first-in-class, phase I study in advanced solid tumors, SGN-2FF demonstrated dose-proportional pharmacokinetics, evidence of pharmacodynamic target inhibition of glycoprotein fucosylation, and preliminary antitumor activity. SGN-2FF was associated with thromboembolic events that led to study termination. Background: We conducted a first-in-human, first-in-class, phase I study of SGN-2FF, a potent small-molecule inhibitor of glycoprotein fucosylation, in patients with advanced solid tumors. Methods: The study consisted of four parts: SGN-2FF monotherapy dose-escalation (part A) and expansion (part B), and SGN-2FF + pembrolizumab dose-escalation (part C) and expansion (part D). The objectives were to evaluate safety and tolerability, maximum tolerated dose (MTD), pharmacokinetics (PK), pharmacodynamics (PD), and antitumor activity of SGN-2FF monotherapy and SGN-2FF + pembrolizumab. Results : Forty-six patients were enrolled (part A, n = 33; part B, n = 6; part C, n = 7; part D did not enroll any patients). During part A ( n = 32) exploring 1–15 g once daily (QD) and 2–5 g twice daily (b.i.d.), grade 3 dose-limiting toxicities were diarrhea (2 g and 15 g QD) and increased lipase (2 g QD). The MTD was 10 g daily. In part A, common toxicities were grades 1–2 diarrhea, fatigue, and nausea (each 47%); thromboembolic events (grades 2–5) occurred in 5 of 32 patients (16%). Safety measures included concurrent prophylactic anticoagulation with low-molecular weight heparin (LMWH). In part C, despite the safety measures implemented, a thromboembolic event occurred in one of seven patients (14%) during the SGN-2FF lead-in period. Of 28 evaluable patients in part A, 1 patient with advanced head and neck squamous cell carcinoma achieved Response Evaluation Criteria in Solid Tumors (RECIST) v1.1 complete response (CR) and 10 (36%) had RECIST v1.1 stable disease, including 1 patient with advanced triple-negative breast cancer with 51% tumor burden reduction. SGN-2FF administration led to dose-proportional increases in exposure and PD reduction in protein fucosylation. Conclusion : SGN-2FF demonstrated proof-of-mechanism and preliminary antitumor activity but was associated with thromboembolic events leading to study termination.